Optimal Stochastic Scheduling - Cai, Xiaoqiang; Wu, Xianyi; Zhou, Xian.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2014)
Many interesting and important results on stochastic scheduling problems have been developed in recent years, with the aid of probability theory. This book provides a comprehensive and unified coverage of studies in stochastic scheduling. The objective is two-fold: (i) to summarize the elementary models and results in stochastic scheduling, so as to offer an entry-level reading material for students to learn and understand the fundamentals of this area; and (ii) to include in details the latest developments and research topics on stochastic scheduling, so as to provide a useful reference for researchers and practitioners in this area. Optimal Stochastic Scheduling is organized into two parts: Chapters 1-4 cover fundamental models and results, whereas Chapters 5-10 elaborate on more advanced topics. More specifically, Chapter 1 provides the relevant basic theory of probability, and then introduces the basic concepts and notation of stochastic scheduling. In Chapters 2 and 3, the authors review well-established models and scheduling policies, under regular and irregular performance measures, respectively. Chapter 4 describes models with stochastic machine breakdowns. Chapters 5 and 6 introduce, respectively, the optimal stopping problems and the multi-armed bandit processes, which are necessary for studies of more advanced subjects in subsequent chapters. Chapter 7 is focused on optimal dynamic policies, which allow adjustments of policies based on up-to-date information. Chapter 8 describes stochastic scheduling with incomplete information in the sense that the probability distributions of random variables contain unknown parameters, which can however be estimated progressively according to updated information. Chapter 9 is devoted to the situation where the processing time of a job depends on the time when it is started. Lastly, in Chapter 10 the authors look at several recent models beyond those surveyed in the previous chapters.
Basic Concepts -- Regular Performance Measures -- Irregular Performance Measures -- Stochastic Machine Breakdowns -- Optimal Stopping Problems -- Multi-armed Bandit Processes -- Dynamic Policies -- Stochastic Scheduling with Incomplete Information -- Optimal Policies in Time-varying Scheduling -- More Stochastic Scheduling Models.                                                                                             .
Keywords: Business; Production management; Operations research; Decision making; Business and Management; Operation Research/Decision Theory; Operations Management